ผลการใช้แนวคิดการเรียนรู้โดยใช้บริบทเป็นฐานที่มีต่อความเข้าใจมโนทัศน์ชีววิทยาของนักเรียนมัธยมศึกษาตอนปลาย - นิ่มละออ พัชรมัย; แก้วดี สกลรัชต์; พลวัฒน์ รสริน (An Online Journal of Education, 2018)
Abstract This study was a quasi-experimental research and used two-group posttest only design. The purposes of this study were to (1) diagnose upper secondary students’ conceptual understanding in biology after learning through context-based learning approach and (2) compare upper secondary students’ conceptual understanding in biology between an experimental group that learned through context-based learning approach and a comparison group that learned through traditional teaching method. The samples of this study were eleventh grade students of a large sized school under the Secondary Educational Service Area Office 2 during the second semester of the academic year 2016. The research instruments were the conceptual understanding in biology test. The collected data was analyzed by mean, means of percentage, standard deviation and t-test. The research findings were summarized as follows: (1) The conceptual understanding in biology mean scores of the experimental group was pass minimum criteria after the experiment and students have the ability to connect concept that can categorized to 4 group as complete concept connection incomplete concept connection partial concept connection and no concept connection (2) The conceptual understanding in biology mean score of the experimental group and comparison group did not differ statistically significant at the .05 level.